The effects of parental loss throughout adolescent stages of development - Spielman, Jade B (Kansas State University, 2007)
Throughout this report, I focused on the effects that the loss of a parent has on an adolescent during the various stages of adolescent development. Drawing upon research already completed on divorce during adolescence, I speculated on the similarities and differences between losing a parent through divorce or death during the adolescent stages of development. Loss by any means is tragic and life altering. However, as I attempted to illustrate, it was even more defining when encountered during the period of adolescence.
Keywords: Adolescence; Parental loss; death; divorce; Health Sciences, Human Development (0758); Health Sciences, Mental Health (0347)